Biological preconditions for the development of the formation concept of spatial organization of body of the children with vision deprivation - Vitaliy Kashuba; Svitlana Savliuk (Kazimierz Wielki University, 2017)
Topicality. Forced decrease in motor activity of children with vision deprivation (VD), concomitant somatic diseases, secondary deviations, disturbances of the musculoskeletal system are steady and significantly restrict the motor capabilities of children with VD, weaken the connection with the outside world, complicate spatial orientation, inhibit psychomotor and physical development of children with VD. Study's objectives: to determine the factor structure of the spatial organization of the body (SOB) of children 6-10 years old with vision deprivation in the physical education process. Research results. The factor structure of the SOB of children 6-10 years old with VD with normal posture is characterized by a certain consistency and, at the same time, certain differences, reflecting changes in the studied parameters. The carried factor analysis of indicators of children 6-10 years old with VD allows to state that the indicators used in the factor analysis procedure is quite informative and provide a full description of SOB of children with VD, because it explain the total variance from 80, 8% to 89, 2%; the change in the contribution of each factors to the overall structure of the SOB of children with VD indicates the change in the significance of different indicators in children of different ages and the need to influence them during the physical education lessons in a special boarding school. Conclusions. The results of factor analysis prove that in the process of studying in a special boarding school, the factors most important for the formation of SOB of children with VD with normal posture are the somatometric component of physical development, the status of the biogeometric profile of posture in the sagittal and frontal plane, functional state and physical fitness: development such important for the formation of the correct SOB physical qualities as - coordination abilities (agility, throwing, vertical stability of the body), strength endurance, flexibility and so on.